The Relationship of Nutritional Status, Physical Activity, Stress, and Menarche to Menstrual Disorder (Oligomenorrhea) - Sekar Arum, Vriska Roro; Yuniastuti, Ari; Kasimi, Oktia Woro (Public Health Perspective Journal, 2019)
Oligomenorrhea is problematic menstrual cycle, which is caused by several factors, including nutritional status, age, physical activity, reproductive diseases and stress. Oligomenorrhea can cause disruption of fertility and emotional stress on the patient.Oligomenorrhea more common in adolescents.Research were purposive sampling method with cross sectional design. The population in this research were students of VocationalHigh Schoolin Brebes consisting of 6school as many as 66 students who have a history of oligomenorrhea and willing to become respondents. The instrument used was a questionnaire. Data analysis using Chi Square test with significance level of 5% (ÃŽÂ± = 0.05) and Multiple Logistic Regression. The results showed no association between nutritional status (p value = 0.002), physical activity (p value = 0.035), stress (p value = 0.037) with oligomenorrhea in adolescents villagevocational schoolin Brebes. There is no relationship menarche (p value = 0.147) with oligomenorrhea in adolescents villagevocational hgh schoolin Brebes. There is a relationship between nutritional status and oligomenorrhea in adolescent at cityschool(p value = 0.000). There is no relationship of physical activity (p value = 0.627), stress (p value = 0.164), menarche (p value = 0.147) with oligomenorrhea in adolescents at cityschool. Teens are expected to be more attention to the factors that can be controlled such as body mass index, physical activity, and stress in order to have regular menstrual cycles that can affect both the health of the female reproductive organs.